The Contributions of In-Service Teacher Training Programmes on Teaching Effectiveness of Kiswahili Subject in Ilala Municipality, Tanzania - Adventina Musiba; Prospery M. Mwila (PT. Pusmedia Group Indonesia, 2024)
Kiswahili teachers in Tanzania lack structured and ongoing in-service training programs (INSET) to improve the effectiveness of their teaching. The study explores the contributions of in-service teacher training programmes (INSET) on the teaching effectiveness of Kiswahili in public secondary schools in Ilala Municipality, Tanzania. Using a mixed-methods approach, the study examines the role of INSET in enhancing teachers’ pedagogical skills, its availability and provision, and the challenges affecting its implementation. A sample of 400 participants was engaged, including teachers, students, and school administrators. Data collection was carried out through a combination of structured questionnaires, interviews, and document analysis. For data analysis, quantitative data were processed using SPSS, while qualitative data were analyzed using thematic analysis. The findings reveal that INSET positively impacts teachers' instructional strategies, increasing their ability to utilise diverse teaching methodologies. However, limited government funding, inadequate institutional support, and low participation hinder the programme’s effectiveness. The study recommends structured professional development initiatives to strengthen Kiswahili teaching and learning outcomes. This research makes an important contribution in understanding the role of INSET (In-Service Training) on the effectiveness of Kiswahili teaching in Tanzania, particularly in Ilala Municipality. The recommendations from this research are expected to provide a feedback mechanism and continuous evaluation should be integrated into the INSET program to ensure its relevance and effectiveness.